Coexistence of Jahn-Teller effect and AFM in two-orbital model for s±-wave iron based superconductors. (January 2021) - Pradhan, B.; Parida, P.K.; Sahoo, S.
Abstract: The origin of pairing mechanism and the coexisting order parameters in F e -based superconductors have been attracting increasing attention. The tetragonal to orthorhombic phase transition which leads the antiferromagnetic phase transition in many F e -based superconductors is one of the current heat discussions of electronic order. The distortion and antiferromagnetism coexist in the phase diagrams of such superconductors. A tight-binding two band model with the coexistence of Jahn-Teller distortion and antiferromagnetism is being proposed here for s ± -wave pairing symmetry of the form c o s k x × c o s k y in the mean field approximation. The model is solved by Zubarev's double-time Green's function technique to find their self-consistent gap equations. Then these gap equations are solved self-consistently numerically and the specific heat, density of states and band energies are studied for the system. Highlights: A Hamiltonian for Fe based SCs with JT and AFM interactions is proposed. The interplay of the gap parameters are studied. The gap values are observed through DOS plots. Specific heat jumps are observed at the transition temperatures. Band energies are also studied.